Pemasangan Instalasi Pompa Hidram Pada Bendungan Rawa Sungai Desa Lalouesamba, Kecamatan Lalembuu, Kabupaten Konawe Selatan - Agustan Agustan; Edward Ngii; Adris Ade Putra; Lawalendo Lawalendo; Ridwansyah Nuhun; Rudi Balaka (Jurnal Pengabdian Masyarakat Ilmu Terapan, 2023)
Lalouesamba Village has the potential for a swamp river to flow which never dries up throughout the season, while the number of villagers increases every year and the area of the village continues to grow. To anticipate these sources of water demand, this service aims to install hydram pump installations on the swamp river dam in question. The stages of its implementation are a) preparation of materials, b) field measurement survey, c) repair of swamp river dam bunds, d) sluice gate work, e) pump assembly, f) installation of pipe installation and pump holders, g) testing and measurement of yield discharge hydram pump, h) installation of hose lines, i) handover of assets to the village. The survey results obtained that the distance between the pump and the settlement was around 400 meters with a height of 14 meters from the surface of the swamp water. The repair of the weir raised the water level by about 50 cm. Meanwhile, the hydram pump installation was able to function as planned and produce a burst discharge of 1 liter per 4 seconds. The hose was installed as far as 400 m. The hydram pump asset installation was handed over to the village head of Lalouesamba to be cared for and used properly